2013
DOI: 10.1155/2013/428582
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Human Papillomavirus and the Human Papillomavirus Vaccine: Knowledge and Attitudes among People of African Descent

Abstract: Objective. To compare knowledge and attitudes of human papillomavirus (HPV) and the vaccine between different cultures of African descent. Methods. A cross-sectional survey of 555 African-Americans and Afro-Caribbeans residing in the US and the Bahamas (BHM) was conducted. Results. General knowledge about HPV and the HPV vaccine differed between the two countries significantly. Bahamian respondents were less likely to have higher numbers of correct knowledge answers when compared to Americans (Adjusted Odds Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
2
12
0
4
Order By: Relevance
“…Parents whose children are not vaccinated continue to cite safety concerns as a reason to deny or delay this vaccine, including concerns about the possibility of lasting health problems for girls [31,56,59]. For example, concerns regarding side effects and fear that the HPV vaccine would be dangerous to her daughter were among the top three reasons given for not vaccinating their child among a national sample of mothers [25].…”
Section: Safety Concerns Among Parents and Adolescentsmentioning
confidence: 99%
“…Parents whose children are not vaccinated continue to cite safety concerns as a reason to deny or delay this vaccine, including concerns about the possibility of lasting health problems for girls [31,56,59]. For example, concerns regarding side effects and fear that the HPV vaccine would be dangerous to her daughter were among the top three reasons given for not vaccinating their child among a national sample of mothers [25].…”
Section: Safety Concerns Among Parents and Adolescentsmentioning
confidence: 99%
“…1,14 Di Indonesia, 96,1% orang tua bersedia anaknya divaksinasi. 15,16 Para remaja di Yogyakarta beralasan perlu berdis- 10 Persetujuan orang tua adalah hal yang sangat penting. Hal ini sesuai budaya yang berlaku di Indonesia bahwa pemegang keputusan utama dalam tindakan anak adalah orang tua.…”
Section: Pembahasanunclassified
“…Beberapa kepustakaan menunjukkan bahwa kebanyakan orang tua akan memberikan persetujuan vaksinasi apabila telah memahami risiko dan manfaat vaksinasi. 15 Faktor lain yang dipertimbangkan adalah rekomendasi dari IDAI dan efektivitas vaksin HPV. Beberapa penelitian sebelumnya merangkum penolakan vaksinasi disebabkan oleh persepsi bahwa vaksin tidak diperlukan karena mereka tidak memiliki risiko, tidak memperoleh rekomendasi dari dokter atau tenaga medis lain untuk memberikan vaksinasi, khawatir akan keamanan dan efek samping vaksin, serta pengetahuan yang rendah tentang vaksin HPV.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…In Honduras, among 632 mothers interviewed in a primary care setting, only 13% had heard of HPV vaccination despite having received information regarding CC awareness . Survey studies from the Bahamas, Guatemala, and Puerto Rico have similarly identified a lack of awareness about HPV infection, its relationship to CC, and the role of the HPV vaccine …”
Section: Limitations Of Existing CC Prevention and Screening Efforts mentioning
confidence: 99%